Identifikasi Tumbuhan Lumut di Kawasan Wisata Taman Nasional Bantimurung - Imu, Ulviani Cerlina; Purnamasari, Andi Bida; Liana, Alin (Fakultas MIPA UNM, 2019)
Abstract. This study aims to determine the types of mosses found in the Bantimurung National Park Tourism Area, especially on the riverbank sites to the entrance of Batu Caves. This research was conducted in June-August 2018. Exploration and collection of specimens was carried out using the roaming method. The specimens obtained were identified using a plant identification book. The results of this study indicate that there are five species of mosses found in the Bantimurung National Park Tourism Area, namely: Thuidium sp., Polytricum Commune, Aulacomnium palustre, Orthotrichum sp., And Ectropothecium sp. The five species come from different families. Keywords: moss, identification, bantimurung national park.